Distribution Of Air Pollution In Parit Raja Focused On Particulate Matter 2.5 (PM2.5) Caused By Industrial Activities - Mohd Rais, Nurul Nasuha; Mohd Kamil, Nor Amani Filzah (Recent Trends in Civil Engineering and Built Environment, 2022)
Particulate matter (PM) consists of a solid complex mixture and suspended of liquid particles in the ambient air. There were nine of factories operated in Parit Raja that emitted many air particles and gaseous pollutants that may cause irritation of respiratory tracts and lungs for residents live near to the area. The overall goal of this research was to analyze the distribution of particulate matter 2.5 (PM2.5) in ambient air surrounding of industrial areas in Parit Raja. There were 27 sampling locations that chosen in this study with the area for each sampling location was 0.16 km² and the total area for these sampling locations were 2.52 km² approximately. PM₂.₅ concentration and meteorological data were measured by using Temtop Airing-1000 Detector and Professional Weather Station device respectively. Air sampling data for these sampling locations were conducted simultaneously on the same day in every an hour for each sampling location which is within 24 hours. Result shown that the highest concentration of PM₂.₅ with the range from 18.2 to 29.0 µg/m3 at South direction which were at industrial area and residential area such as Taman Ria Baru due to wind direction from emission source pointed to that area and low wind speed. All of the sampling locations must be measured simultaneously within 24 hours to ensure an accurate data of PM2.5 concentration may be achieved.